The representation of material categories in the brain - Jacobs, Richard H.; Baumgartner, Elisabeth; Gegenfurtner, Karl R. (Frontiers in Psychology, 2014)
Using textures mapped onto virtual nonsense objects, it has recently been shown that early visual cortex plays an important role in processing material properties. Here, we examined brain activation to photographs of materials, consisting of wood, stone, metal and fabric surfaces. These photographs were close-ups in the sense that the materials filled the image. In the first experiment, observers categorized the material in each image (i.e., wood, stone, metal, or fabric), while in an fMRI-scanner. We predicted the assigned material category using the obtained voxel patterns using a linear classifier. Region-of-interest and whole-brain analyses demonstrated material coding in the early visual regions, with lower accuracies for more anterior regions. There was little evidence for material coding in other brain regions. In the second experiment, we used an adaptation paradigm to reveal additional brain areas involved in the perception of material categories. Participants viewed images of wood, stone, metal, and fabric, presented in blocks with images of either different material categories (no adaptation) or images of different samples from the same material category (material adaptation). To measure baseline activation, blocks with the same material sample were presented (baseline adaptation). Material adaptation effects were found mainly in the parahippocampal gyrus, in agreement with fMRI-studies of texture perception. Our findings suggest that the parahippocampal gyrus, early visual cortex, and possibly the supramarginal gyrus are involved in the perception of material categories, but in different ways. The different outcomes from the two studies are likely due to inherent differences between the two paradigms. A third experiment suggested, based on anatomical overlap between activations, that spatial frequency information is important for within-category material discrimination.